(untitled) - Swardson, Nick; Giarraputo, Jack; Sandler, Adam; Wachtel, Waddy; Prior, Peck; Solowitz, Sandy; Ackerman, Tom; Bernardi, Barry; 1964-; Covert, Allen; 1978-; 1973-; et al. (Culver City, CA, 2006)
A trio of guys try to make up for missed opportunities in childhood by forming a three-player baseball team to compete against standard little league squads.
Keywords: Best friends; Drama; Little League baseball; Drama; Baseball; Tournaments; Drama; Films for the hearing impaired; Video recordings for the hearing impaired; Sports films; Comedy films; Feature films; DVD-Video discs